MiR-100 rs1834306 A>G Increases Biliary Atresia Risk in Southern Han Chinese Children. (4th January 2023) - Chang, Jiaming; Liang, Jiankun; Chai, Chengwei; Liu, Fei; Tao, Boyuan; Wang, Hezhen; Tong, Yanlu; Wang, Zhe; Xia, Huimin
Abstract : Background . Biliary atresia (BA) is a type of severe cholestatic childhood disease that may have a genetic component. miR-100 plays a key role in regulating cell apoptosis, proliferation, and inflammatory reactions. A single-nucleotide polymorphism in miR-100 has been proven to modulate susceptibility to various diseases. Methods . We conducted a case-control retrospective study to explore the correlation between miR-100 gene polymorphism (rs1834306 A>G) and biliary atresia susceptibility in 484 Chinese patients and 1445 matched control subjects. Results . Our results showed that rs1834306 A>G was correlated with a significantly increased risk for BA (GG vs. AA: adjusted odds ratio OR = 1.44, 95 % confidence interval CI = 1.02 – 2.03, p = 0.041 ; and GG vs. AA/AG: adjusted OR = 1.39, 95 % CI = 1.02 – 1.89, p = 0.036 ). Conclusions . Our results showed that the rs1834306 A>G polymorphism is associated with an increased risk for BA and contributes to BA susceptibility.